Apocalyptic Temporalities and Re-Setting the Future: Using Creative Pedagogies to Explore Everyday Cultures of Grief During Pandemic Times - Madden , Deborah; Drake , Pat; Clifford , Sara (Journal of Public Pedagogies, 2022)
This article provides a metacritical analysis of an oral history and creative arts project undertakencollaboratively by the authors, located in the Centre for Memory, Narrative and Histories at theUniversity of Brighton. The ‘Everyday Cultures of Grief’ project collected reflexive oral historiesfrom palliative care clinicians and practitioners to evaluate ‘everyday’ subjective experiences andemotional responses to COVID-19 and its unequal impacts. Using the Spanish Flu pandemic of1918 as a heuristic device, oral history interviews captured timely perspectives on the differingaffective scales related to illness, dying, anticipatory grief and mourning during pandemic times.Whilst highlighting some of the key themes of this empirical research, the chief purpose of this articleis to reflect on the project’s distinctive methodology, creative pedagogies and digital disseminationduring the UK’s first lockdown. Creative pedagogies were expressed in a range of affectivearticulations, including public history, creative writing and site-responsive theatre performance.The project itself raised questions about uses of the historical past, particularly in the context ofBrexit populism, as well as the hermeneutics of historical inquiry when investigating the emotionalregisters of past and present pandemics.